2022
DOI: 10.3389/fpsyg.2022.976345
|View full text |Cite
|
Sign up to set email alerts
|

Does board diversity reduce the probability of financial distress? Evidence from Chinese firms

Abstract: This paper empirically investigates the impact of cognitive board diversity in education, expertise, and tenure facets on financial distress likelihood in the emerging economy of China. This study examines how this relationship varies across State-Owned Enterprises (SOEs) and Non-State-Owned Enterprises (NSOEs). Paper argues that the Chinese stock market, as a typical emerging market, is an excellent laboratory for studying the impact of board diversity on the probability of financial distress. Its underdevelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…Endogeneity difficulties in regression models can be caused by a variety of variables, including measurement inaccuracy, simultaneity and reverse causality. Endogeneity can have a major impact on inference and can be removed by using the GMM technique (Lin et al , 2019; Aksoy and Yilmaz, 2023; Ali et al , 2022; Guizani and Abdalkrim, 2023). As a result, the dynamic GMM estimator model was used to study the effect of board diversity on FD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Endogeneity difficulties in regression models can be caused by a variety of variables, including measurement inaccuracy, simultaneity and reverse causality. Endogeneity can have a major impact on inference and can be removed by using the GMM technique (Lin et al , 2019; Aksoy and Yilmaz, 2023; Ali et al , 2022; Guizani and Abdalkrim, 2023). As a result, the dynamic GMM estimator model was used to study the effect of board diversity on FD.…”
Section: Methodsmentioning
confidence: 99%
“…However, such studies are inconclusive and cannot be applied to an emerging economy like Pakistan due to large differences in financial, accounting and economic systems (as cited in Altman et al , 2007; Zhang et al , 2013). Third, empirical research has found a link between board diversity and the risk of FD (Ali et al , 2022; Yousaf et al , 2021; Kristanti et al , 2016; Manzaneque et al , 2016). Although researchers suggested that mediating variables be investigated to determine how board diversity improves firm performance (Harjoto et al , 2019; Miller and Triana, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…When competitive uncertainty is low, a firm's competitive environment is stable and external risk is predictable (Ali et al, 2022a). CEOs with high self-oriented perfectionism can pay adequate attention to thoroughness and detail and identify valuable information for decision-making.…”
Section: 11mentioning
confidence: 99%
“… Ali et al (2022) asserted the significance of the multifunctionality of the board in reducing the distress situation of the firm. The board diversity benefits the firm during the interim meetings.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%